2017
DOI: 10.1002/jmri.25699
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of PDFF estimation by magnitude‐based and complex‐based MRI in children with MR spectroscopy as a reference

Abstract: Purpose To assess and compare the accuracy of magnitude-based MRI (MRI-M) and complex-based MRI (MRI-C) for estimating hepatic proton density fat fraction (PDFF) in children, using magnetic resonance spectroscopy (MRS) as the reference standard. A secondary aim was to assess the agreement between MRI-M and MRI-C. Methods This was a HIPAA-compliant, retrospective analysis of data collected in children enrolled in prospective, IRB-approved studies between 2012 and 2014. Informed consent was obtained from 200 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Further research is needed to confirm and explain the discrepancy in R2* estimation by MRI‐M and MRI‐C in the low R2* range. The slight underestimation of PDFF by MRI‐M is consistent with previous studies …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further research is needed to confirm and explain the discrepancy in R2* estimation by MRI‐M and MRI‐C in the low R2* range. The slight underestimation of PDFF by MRI‐M is consistent with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…We selected children because they rarely have excess hepatic iron and are an ideal population to determine the relationship between PDFF and R2* unconfounded by iron content. A secondary purpose of the study was to evaluate the agreement between MRI‐M and MRI‐C for estimating R2* values in human subjects, and to validate the high agreement between these techniques reported in prior studies for estimating PDFF …”
mentioning
confidence: 88%
“…In our study, although small, there was an overestimation in CSE‐PDFF compared with MRS‐PDFF as indicated by an intercept of 1.74 and a mean bias of 3.4 PDFF%. Several studies have described minimal overestimation by CSE‐MRI, more so in the 1.5 T, than by MRS, while in a meta‐analysis CSE‐MRI slightly underestimated the MRS . Overestimation by CSE‐MRI could reflect residual T 1 bias, particularly as the parameters used in our study (TR = 8.9 msec and flip angle = 5° at 1.5 T) can induce ~2% of fat fraction measurement error .…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have described minimal overestimation by CSE-MRI, more so in the 1.5 T, than by MRS, 30,31 while in a meta-analysis CSE-MRI slightly underestimated the MRS. 22 Overestimation by CSE-MRI could reflect residual T 1 bias, particularly as the parameters used in our study (TR = 8.9 msec and flip angle = 5 at 1.5 T) can inducẽ 2% of fat fraction measurement error. 30,32 Also, including all measurements from different field strengths/2-week interscan period and using a phased array coil identical to the one used in the clinical scan might have contributed to field inhomogeneity in the non-anthromorphologic phantom, resulting in greater measurement bias. 33 Additionally, because the CSE-MRI technique in the current study employed spectral models of fat based on body temperature, CSE-PDFF of the phantom with lower temperature (16-20 C) could deviate from MRS-PDFF.…”
Section: Discussionmentioning
confidence: 86%
“…An increasing number of studies have shown MRE to be an accurate method for diagnosing and staging hepatic fibrosis in patients with NAFLD (Table 4 ). Among the studies using MRE, the AUROC for diagnosis of stages > 1, > 2, > 3, and 4 ranged from 0.772 to 0.860, 0.856 to 890, 0.870 to 0.981, and 0.882 to 0.993, respectively [ 62 , 63 , 81 , 93 98 ]. The corresponding MRE liver stiffness cut-offs for mild fibrosis (stage > 1) or advanced fibrosis (stage > 3) ranged from 2.50 to 3.02 kPa or 2.99 to 4.80 kPa with a sensitivity of 44–75% or 33–91% and specificity of 77–91% or 80–94%, respectively.…”
Section: Magnetic Resonance Elastographymentioning
confidence: 99%